Introgressive hybridization of Schistosoma haematobium group species in Senegal: species barrier break down between ruminant and human schistosomes. - Bonnie L Webster; Oumar T Diaw; Mohmoudane M Seye; Joanne P Webster; David Rollinson (Public Library of Science (PLoS), 2013)
BACKGROUND: Schistosomes are dioecious parasitic flatworms, which live in the vasculature of their mammalian definitive hosts. They are the causative agent of schistosomiasis, a disease of considerable medical and veterinary importance in tropical and subtropical regions. Schistosomes undergo a sexual reproductive stage within their mammalian host enabling interactions between different species, which may result in hybridization if the species involved are phylogenetically close. In Senegal, three closely related species in the Schistosoma haematobium group are endemic: S. haematobium, which causes urogenital schistosomiasis in humans, and S. bovis and S. curassoni, which cause intestinal schistosomiasis in cows, sheep and goats. METHODOLOGY/PRINCIPAL FINDINGS: Large-scale multi-loci molecular analysis of parasite samples collected from children and domestic livestock across Senegal revealed that interactions and hybridization were taking place between all three species. Evidence of hybridization between S. haematobium/S. curassoni and S. haematobium/S. bovis was commonly found in children from across Senegal, with 88% of the children surveyed in areas of suspected species overlap excreting hybrid miracidia. No S. haematobium worms or hybrids thereof were found in ruminants, although S. bovis and S. curassoni hybrid worms were found in cows. Complementary experimental mixed species infections in laboratory rodents confirmed that males and females of each species readily pair and produce viable hybrid offspring. CONCLUSIONS/SIGNIFICANCE: THESE DATA PROVIDE INDISPUTABLE EVIDENCE FOR: the high occurrence of bidirectional hybridization between these Schistosoma species; the first conclusive evidence for the natural hybridisation between S. haematobium and S. curassoni; and demonstrate that the transmission of the different species and their hybrids appears focal. Hybridization between schistosomes has been known to influence the disease epidemiology and enhance phenotypic characteristics affecting transmission, morbidity and drug sensitivity. Therefore, understanding and monitoring such inter-species interactions will be essential for optimizing and evaluating control strategies across such potential hybrid zones.